The Effect of Leverage, Profitability and Firm Size on Tax Avoidance Pre and During the Covid-19 Pandemic: Case Study on Property, Real Estate and Building Construction Sector Companies Listed on The Indonesia Stock Exchange 2016-2020 Period - Sendi Gusnandar Arnan; Chandra Kurnia (Pusat Penelitian dan Pengabdian Pada Masyarakat (P3M) STIE Pasundan, 2022)
Tax avoidance is an act that is detrimental to the state and is often done by companies. For this reason, researchers want to find out more about the effect of leverage, profitability, and firm size on tax avoidance before and during the COVID-19 pandemic by studying literature on Property, Real Estate, and Building Construction sector companies listed on the Indonesia Stock Exchange for the 2016-2020 period. The method used is literature study and internet research with a sample of 19 companies. Determination of the sample using a purposive sampling technique that is tailored to the research objectives. The results of the study are that leverage has a significant effect on tax avoidance before the covid-19 pandemic and during the covid-19 pandemic, leverage does not affect tax avoidance. While profitability is known to have a significant influence both before and during the covid-19 pandemic, and on the firm size factor, this factor has a significant influence on tax avoidance before covid-19 takes place and has no effect during covid-19.